PERANCANGAN DAN IMPLEMENTASI SISTEM INFORMASI MANAJEMEN ASET PADA PEMERINTAH KABUPATEN MERANGIN MENGGUNAKAN BAHASA PEMROGRAMAN PHP DAN MYSQL - sularno Larno; Nori Sahrun (Prodi Sistem Informasi Universitas Dharma Andalas, 2019)
Asset managements is most needed by every businessm especially in recording asset at the local government agencies. Setting is done so that each asset procurement of equipment and goods in these institutions can be properly maintained. In the presence of an inegrated asset management system within the scope of government Merangin to perform data collection and monitoring of assets that can be used as guidelines for decision-making in procurement and rejuvenation of government asset.